A fusion product of the complete Borrelia burgdorferi outer surface protein A (OspA) and the hepatitis B virus capsid protein is highly immunogenic and induces protective immunity similar to that seen with an effective lipidated OspA vaccine formula - Nassal, Michael; Skamel, Claudia; Kratz, Peter A.; Wallich, Reinhard; Stehle, Thomas; Simon, Markus M. (European journal of immunology, 2005)
The immunogenicity of peptides and protein fragments can be considerably enhanced by their presentation on particulate carriers such as capsid-like particles (CLP) from hepatitis B virus (HBV). Here we tested the suitability of the HBV capsid protein as a carrier for a relevant full-length pathogen-derived protein antigen. The entire 255-amino acid ectodomain of the outer surface protein A (OspA) from Borrelia burgdorferi, the causative agent of Lyme disease, was inserted into the major B cell epitope of the HBV capsid, yielding a multimerization-competent fusion protein, termed coreOspA. CoreOspA, consisting only in part of regular CLP, induced antibodies to OspA, including the Ig isotype profile and specificity for the protective epitope LA-2, with an efficiency similar to that of recombinant lipidated OspA, the first generation vaccine against Lyme disease. Moreover, coreOspA actively and passively protected mice against subsequent challenge with B. burgdorferi. The data demonstrate the capacity of the HBV capsid protein to act as a potent immunomodulator even for full-length and structurally complex polypeptide chains and thus opens new avenues for novel vaccine designs.
Gesehen am 04.06.2021